Deep Learning–Driven Prediction of Early Functional Recovery After Femoral and Sciatic Nerve Block in Knee Arthroscopy Patients - Michael R. Bennett; Baphia Yurner; Bhrispher Fitzberald (International Journal of Clinical and Translational Medicine, 2026)
Early functional recovery following knee arthroscopy is a critical determinant of postoperative outcomes, healthcare resource utilization, and patient satisfaction. Femoral and sciatic nerve block techniques have become widely adopted regional anesthesia strategies because of their ability to provide effective perioperative analgesia while reducing opioid consumption and facilitating rehabilitation. Despite their clinical advantages, substantial heterogeneity remains in postoperative recovery trajectories among patients receiving similar anesthetic interventions. Traditional risk assessment methods often fail to capture complex interactions among demographic characteristics, perioperative variables, physiological indicators, and rehabilitation-related factors. Recent advances in deep learning provide opportunities to develop predictive systems capable of modeling nonlinear relationships within multidimensional clinical environments. This study presents a system-oriented framework for deep learning–driven prediction of early functional recovery after femoral and sciatic nerve block in knee arthroscopy patients. Rather than focusing solely on predictive accuracy, the research examines architectural design principles, multimodal data integration strategies, model governance requirements, deployment considerations, fairness implications, and healthcare infrastructure challenges. The proposed framework integrates electronic health records, perioperative monitoring streams, rehabilitation assessments, and patient-reported outcomes into a unified predictive ecosystem. Deep neural architectures are evaluated as decision-support mechanisms capable of identifying recovery trajectories during the immediate postoperative period. The findings suggest that deep learning systems can substantially enhance individualized recovery prediction while supporting more efficient allocation of rehabilitation resources. However, successful implementation requires careful attention to data quality, explainability, operational resilience, ethical governance, and institutional interoperability. The study contributes a comprehensive perspective on how artificial intelligence can be embedded within perioperative care systems to improve outcome forecasting and advance precision rehabilitation strategies in orthopedic surgery environments.